The legal foundations of public administration - Barry, Donald D. (West Pub. Co., 1987)
The third edition of this highly respected textbook introduces students of public administration to the practical issues of administrative law. While useful to law school students, it is most relevant to public management students. The presentation provides a concise foundation to the history and theory of administrative law, rule making, and judicial decisions. The most important issues in administrative law are included--meaningful issues for present and future administrators. A larger number of recent cases and other up-to-date information will be found in the book in order to make the student aware of the kinds of legal problems likely to be encountered in public agencies. One or two cases illustrate each problem at hand, rather than discussing numerous arcane court decisions and technicalities of legal procedure, in order to sketch the broad contours of the present law